Dynamics of Interferon-G and Interleukine-4 levels in serum of patients with chronic hepatitis C with mixed cryoglobulinemia on the background of immunomodulatory therapy - O. P. Mashko; O. V. Ryabokon (Zaporožskij Medicinskij Žurnal)
It is shown that inclusion of erbisol into the complex pathogenetic treatment of chronic hepatitis C with mixed cryoglobulinemia helps to restore cytokine balance by increasing concentrations of interferon-γ and decreasing of interleukin-4 in blood serum, helps to decrease cryocrit level, to reduce cytolysis syndrome and clinical manifestations of cryoglobulinemic syndrome.